Relationship Between the Monthly Allowance and Daily Expenses Among UiTM Jengka Students - Nurul Nadiya Abu Hassan; Nurmarni Athirah Abdul Wahid (RIRAI Publisher, 2023)
Nowadays, a lot of universities students tend to live independently whether is the hostel or a rental house. Most students would manage their financial themselves and they get their financial help from either National Higher Education Fund Corporation (PTPTN), scholarships, their own saving or family funding. Several previous studies has been conducted based on students financial and some of it are on students awareness on their financial management. There are studies on students spending expectations and habits, also the relationship between monthly allowance and their average grade. Hence, a study on relationship between monthly allowance and their daily spending is done. This research took place in Universiti Teknologi Mara Jengka, Pahang (UCPh) where the researchers conducted a type of Quantitative Survey Research of gathering data. There is total 152 students that were involved in this research and they were from the various faculties in UCPh. After running the data gathered through IBM SPSS Statistics 25 Software, by using the Pearson correlation approach, it can be concluded that there is no significant relationship between the monthly allowance and their daily spending